(untitled) (Damascus University Journal of agriculture sciences, 2024)
This study was carried out in the nursery of the administration of the industrial city in Adra of Rif Damascus, during the agricultural season 2020/2021, with the aim of studying the effect of irrigation with wastewater of some sectors in the city on the growth of the barley crop and the soil grown in it, depending on the crop irrigation with different mixing ratios of groundwater, treated and non-treated wastewater. Treatment and on some indicators as: plant height, number of plants per square meter, number of grains per plant, weight of grains per plant, dry weight of the plant, weight of a thousand grains, grain yield, vital yield, harvest guide. The experiment was designed using a simple random design method, with three replications for each irrigation treatment. The results showed a noticeable difference between irrigation treatments with treated and untreated water, and an increase in some chemical indicators in the soil such as (Electric Conductivity EC, Dissolved Sulfur SO4-2, Chemical Oxygen Requirement COD, Biological Oxygen Requirement BOD and Chlorine Cl-1) when irrigating the crop with treated water, the values (20400 µS/cm, 7000 mg/L, 1860 mg/L, 968 mg/L, 7100 mg/L) were respectively more than irrigating it with untreated water where the values were (22150 µS/cm, 6830 mg/L) , 712 mg/l, 417 mg/l, 1827 mg/l) respectively. With untreated water, irrigation treatments with untreated water outperformed irrigation with treated water in most of the studied indicators. The concentration of heavy metals in soil and plants increased above the normal and permissible limit and was within the toxic content. The highest protein content was in barley grains irrigated with untreated water (10.40). The lowest percentage of protein in barley grains irrigated with treated water was .% (7.7)